Bonhoeffer’s understanding of state-church relationship in context - Stephen Phiri (Cogent Arts & Humanities)
A man imbued with unfathomable passion and belief in Christ confronts a merciless regime, which he believed has acted beyond the bounds of divine mandates. His confrontation of this regime was relentless until the regime condemned him to the sword. The understanding of Bonhoeffer’s church-state relationship as expressed in one of his iconic books ‘Ethics’ is a response to the gross violation by Hitler when he failed to justly rule the government mandate and further his imposition of policy on the church with the objective of promoting his tyrannical agenda. This article seeks to understand Bonhoeffer’s church and state model through his existential circumstances of Adolf Hitler’s reign. It uses literature reviewed on both Bonhoeffer’s primary writings such as ‘Ethics’ and secondary sources that sought to comment and give an analysis of his thoughts. The article highlights the unique and radical position of Bonhoeffer’s theo-political stance over both the Barmen declaration and efforts made by the Confession church.